Adult attachment, hostile conflict, and relationship adjustment among couples facing multiple sclerosis - Crangle, Cassandra J.; Hart, Tae L. (British journal of health psychology, 2017)
Objective Couples facing multiple sclerosis (MS) report significantly elevated rates of relationship distress, yet the effects of attachment have never been examined in this population. We examined whether hostile conflict mediated the dyadic effects of attachment on relationship adjustment in couples facing MS and whether these associations were moderated by gender or role. We also explored whether dyadic adjustment mediated the relationship between attachment and hostile conflict. Design The study was cross‐sectional and included 103 couples in which one partner had been diagnosed with MS. Methods Participants completed the Experiences in Close Relationships‐Revised, Dyadic Adjustment Scale, and Aversive Interactions Scale, as well as demographic variables. We used the actor–partner interdependence model for data analysis. Results There were significant actor and partner effects of greater anxious attachment and worse dyadic adjustment. Actor and partner effects of anxious attachment were significantly mediated by greater hostile conflict. Gender significantly moderated the effects between avoidant attachment and dyadic adjustment. The actor effect was significant for males and females; the partner effect was only significant for females. The actor effect for females but not males was significantly mediated by greater hostile conflict. Role was not a significant moderator. Exploratory analyses also showed that dyadic adjustment mediated the relationship between anxious and avoidant attachment and hostile conflict. Conclusions Findings highlight the important effects of attachment on relationship adjustment in MS couples. Both hostile conflict and dyadic adjustment appear to be mechanisms through which insecure attachment has a detrimental effect. Statement of contribution What is already known on this subject? Despite higher‐than‐normal rates of marital distress and separation/divorce, the effects of attachment on relationship adjustment among couples facing multiple sclerosis have never been examined. Prior studies within healthy populations have supported within‐person and cross‐dyadic associations between attachment and relationship adjustment; however, they have failed to use dyadic analyses. Hostile conflict has been associated with both insecure attachment and relationship adjustment and therefore may be an important mediator to help understand these relationships. What does this study add? Women were more negatively affected by their partner's avoidant attachment then men. Hostile conflict mediated the effects of anxious attachment on dyadic adjustment for individuals and across dyads. Hostile conflict accounted for the individual effect of avoidant attachment on dyadic adjustment for women.